2004
DOI: 10.1093/jac/dkh380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lysophospholipid analogues edelfosine, ilmofosine and miltefosine against Leishmania amazonensis

Abstract: The alkylglycerophosphocholines edelfosine and ilmofosine were more active than the alkylphosphocholine miltefosine against promastigotes and intracellular amastigotes of L. amazonensis, and ultrastructural and flow cytometry data indicate the mitochondrion as a target of edelfosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 25 publications
10
68
1
Order By: Relevance
“…The reported IC 50 value for the treatment of intracellular amastigotes of Leishmania amazonensis with miltefosine in vitro was 9 mM (3.6 mg ml 21 ) (Santa-Rita et al, 2004), which is higher than the MIC values of 2.5-5 mM (1-2 mg ml 21 ) reported here for the treatment of S. brasiliensis isolates. Therefore, our results indicate that lower miltefosine doses than those used against human leishmaniasis could be effective in the treatment of sporotrichosis.…”
Section: Discussioncontrasting
confidence: 64%
“…The reported IC 50 value for the treatment of intracellular amastigotes of Leishmania amazonensis with miltefosine in vitro was 9 mM (3.6 mg ml 21 ) (Santa-Rita et al, 2004), which is higher than the MIC values of 2.5-5 mM (1-2 mg ml 21 ) reported here for the treatment of S. brasiliensis isolates. Therefore, our results indicate that lower miltefosine doses than those used against human leishmaniasis could be effective in the treatment of sporotrichosis.…”
Section: Discussioncontrasting
confidence: 64%
“…Several studies have demonstrated changes in the mitochondria morphology of some Leishmania spp. previously treated with antileishmanial agents (Delorenzi et al, 2001;Santa-Rita et al, 2004;Ueda-Nakamura et al, 2006;Rodrigues et al, 2007;Santos et al 2008). These studies reported that significant alterations in the mitochondria led to the loss of cell viability and confirmed the importance of this organelle in the viability of L. infantum (Fonseca-Silva et al, 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, miltefosine has been successfully used to treat patients with antimony-resistant VL, VL in children and CL in South America (Croft & Engel 2006 (Escobar et al 2002, Santa-Rita et al 2004, CabreraSerra et al 2007). In addition, the induction of apoptosis following miltefosine treatment has already been reported in L. donovani (Paris et al 2004, Verma et al 2007).…”
mentioning
confidence: 99%
“…The ultrastructural analysis of edelfosine-treated promastigotes and amastigotes indicated the mitochondrion as the main target. However, plasma membrane alterations and autophagic structures were detected in promastigotes (Santa-Rita et al 2004). The activity of these compounds was evaluated against L. amazonensis using an in vivo mouse model, which showed that perifosine was the most effective compound.…”
mentioning
confidence: 99%